Efektifitas Material Akustik Pengendali Kebisingan pada Ruang Genset di Pusat Perbelanjaan di Gorontalo - Haisah Siti; Indah Sari Zulfiana (JST (Jurnal Sains Terapan), 2018)
Shopping centers construction have to do a good building management so it would have a comfort for visitors. One of comfort things that should get the attention is audial comfort. In Gorontalo City, Most of the electricity users choose to use electricity from Generator set supply, this results an increase in noise. The rotors of the electrical generators basically can be controlled by the use of box silent that has been specially designed so that it can prevent noise. In addition on the control of noise to the same type of chambers electrical generators may also be convened with arranging in layer interior of the same type of chambers with the material acoustic absorbed sound. The use of acoustic material sound-absorbent can work effectively with right material, in accordance with the degree of hardness sound taking place in the room. This research takes the generator chamber in one of shopping centers in Gorontalo. Generator chamber in this study has been tasted in two treatment tests of space generator. In first test, the wall of the coated material dampers from Styrofoam with thickness 2 cm, and obtained percent reduction noise of 8,32 % , While in the second test by using layers Styrofoam and rugs are able to reduce noise into 17,58 %. The final result of the research found is that the previous noise of 95db can be reduced to 78,3db.